State-Owned Banks and Fiscal Discipline - Gonzalez-Garcia, Jesus (IMF Working Papers; Working Paper ;, 2013)
State-owned banks may help to soften the financing constraints of public sector entities and consequently become a factor that hampers fiscal discipline. Using a panel dataset, we find that a larger presence of state-owned banks in the banking system is associated with more credit to the public sector, larger fiscal deficits, higher public debt ratios, and the crowding out of credit to the private sector. These results suggest that the lending practices of state-owned banks should be carefully assessed in any strategy to pursue fiscal discipline.